Improving Emergency Skills: Training Program at Medono Health Center, Pekalongan City - Arief Sulistyanto, Benny; Wirotomo, Tri Sakti; Ramadani, Nur Indah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
First aid is crucial and essential for providing emergency assistance. Early treatment of injured individuals at home can significantly reduce morbidity and mortality rates. Community health center staff, as primary service providers to the community, must be proficient in first aid since emergencies can happen anytime and anywhere. This study assessed the effectiveness of Cardiopulmonary Resuscitation (CPR) training at the Medono Community Health Center in enhancing the knowledge and skills of healthcare workers. Initially, 76.2% of participants had inadequate knowledge about CPR, but after training, 86% showed a substantial improvement in knowledge. Furthermore, the training reduced errors in using the Bag Valve Mask (BVM) and performing chest compressions. Mistakes in ventilation decreased after proper instruction, and errors in compression positioning dropped from 57.8% to nearly zero. These findings highlight the critical role of CPR training in enhancing the preparedness and competence of healthcare workers in emergencies. The Medono Health Center is dedicated to regularly conducting CPR training to ensure the continuous improvement of healthcare quality and patient safety.